Extraterritoriality : locating Hong Kong cinema and media - Fan, Victor (Edinburgh scholarship online, 2019)
Examining how Hong Kong filmmakers, spectators and critics wrestled with this perturbation between the Leftist Riots (1967) and the aftermath of the Umbrella Movement (2014), this book traces how Hong Kong's extraterritoriality has been framed: in its position of being doubly occupied and doubly abandoned by contesting juridical, political, linguistic and cultural forces. Extraterritoriality scrutinises creative works in mainstream cinema, independent films, television, video artworks and documentaries - especially those by marginalised artists - actively rewriting and reconfiguring how Hong Kong cinema and media are to be defined and located